COMPARISON OF THE FINANCIAL PERFORMANCE OF COMPANIES USING CONVENTIONAL ACCOUNTING METHODS AND ACCRUAL-BASED ACCOUNTING - Dessy Evianti; Renika Hasibuan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research is a systematic literature review aimed at comparing the financial performance of companies based on the use of conventional accounting methods (cash basis) and accrual-based accounting. The fundamental difference between the two methods lies in the timing of transaction recognition, which directly impacts the presentation of financial statements and performance indicators such as Return on Assets (ROA), Return on Equity (ROE), profit margins, and solvency. The synthesis of various studies shows that the accrual method provides more complete, relevant financial information and reflects the economic reality of the company more accurately compared to the conventional method. Additionally, accrual-based accounting has been proven to enhance transparency, accountability, and managerial efficiency, especially in the public sector and large-scale companies. However, the effectiveness of its implementation is greatly influenced by technical readiness, institutional capacity, and policy support. This study recommends that the selection of accounting methods be adjusted to the information needs of report users, the complexity of the organization, and the objectives of financial reporting. Thus, this research is expected to serve as a basis for consideration in the reform of financial reporting systems across various sectors.